A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan, China - Li, Guo-Feng; Wang, Chun-Mei; Li, Hua-Feng; Hou, Yun-Ping (Zootaxa, 2015)
Oxyporus (Oxyporus) bingshengae sp. nov. in Yunnan, China, is described. Color images of the habitus and aedeagus of the new species are included. A key to the species of Oxyporus of Yunnan is provided.